2000
DOI: 10.1017/s0026749x0000384x
|View full text |Cite
|
Sign up to set email alerts
|

Distant Thunder: The Regional Economies of Southwest China and the Impact of the Great Depression

Abstract: A study of the impact of the 1930s World Depression on Southwest China intersects with two major controversies in modern Chinese economic history. First, there is still substantial disagreement over the severity of the impact of the Depression on China. The ‘traditional’ interpretation inside China has focused on the ‘bankruptcy’ of the economy in the 1930s (of which the Depression was one but not the only cause). While many aspects of the ‘bankruptcy’ and ‘stagnation’ theses have more recently been di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Agricultural regions varied in their degree of commercialization and susceptibility to external market fluctuations. Many interior areas, as Wright's (2000) study of the southwest shows, remained weakly commercialized and did not experience serious economic dislocations caused by the global economic crisis. As far as north China is concerned, Myers (1971:278) states:…”
Section: “The Nanking Decade”mentioning
confidence: 99%
“…Agricultural regions varied in their degree of commercialization and susceptibility to external market fluctuations. Many interior areas, as Wright's (2000) study of the southwest shows, remained weakly commercialized and did not experience serious economic dislocations caused by the global economic crisis. As far as north China is concerned, Myers (1971:278) states:…”
Section: “The Nanking Decade”mentioning
confidence: 99%
“… Fox 1994, e.g, explicitly argues against the notion of fast-equilibrating inter-provincial labour and commodity markets that Brandt and Rawski propose for early twentieth-century China. Though broadly in the same church as Rawski, Wright too observed that Chinese factor markets did not function well in the hinterland(Wright 2000). In her newly published monumental work, LillianLi (2007, pp.…”
mentioning
confidence: 99%
“…34 He commented that the Xikang languages are "easy to learn but difficult to master" and provided readers with some introductory sentences in Xikang tujing. 35 According to Ren, all the Han who went to Xikang soon learnt such phrases and, after one or two years, could conduct conversations in the local tongues. 36 (Those in higher leadership posts appear to have been the exception: "It is unheard of for Han governors to be able to understand Fan [Tibetan] languages."…”
Section: Sourcesmentioning
confidence: 99%
“…In 1939 the 34 Ren Naiqiang, Xikang tujing: minsu pian 西康图经: 民俗篇 (Shanghai: Shanghai shudian, 1996Shanghai shudian, [1933), 204. 35 Ibid.…”
Section: Sourcesmentioning
confidence: 99%
See 1 more Smart Citation